Pengaruh Profesionalisme Auditor, Independensi dan Etika Profesi Terhadap Pertimbangan Tingkat Materialitas Akuntan Publik - Rony Polindo; Agus Munandar (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to demonstrate empirically and analyze the influence of the professional auditors, independent and professional ethics on the material considerations of public accountants. Sample from the study included auditors who worked in Central Jakarta, Southern Jakarta and several office of Big Four public accountant, and then the student of the sample using the simple random sampling technique led to 70 auditor of 38 public accountant. This study uses the help of SPSS programs 25 and Microsoft Office Excel in processing information that eventualy leads to accounting. The method used by the study is regression tests, F test and T tests. The results of this study are the professionalism auditors, independent and professional ethics of the profession affect consideration of materiality.